Jamur dari Mangrove sebagai Sumber Senyawa Metabolit Sekunder Bioaktif yang Berpotensi sebagai Kandidat Antikanker: Review Literatur - Kristiani, Ni Kadek Ari; Putra, I Putu Yogi Astara; Putri, Ni Wayan Prasanthi Swarna; Leliqia, Ni Putu Eka; Ujam, Nonye Treasure; Ariantari, Ni Putu (Jurnal Ilmiah Medicamento, 2023)
Cancer was the leading cause of death, which accounting for nearly 10 million deaths globally in 2020. Currently, cancer treatment still relies on chemotherapy, however, most anticancer drugs showed non-specific toxicity to normal cell proliferation resulting in various side effects, and are ineffective against many forms of cancer. In addition, the increasing case of chemoresistance of cancer cells to chemotherapy has boosted the discovery of new anticancer agents. Natural products are known as the origin of several clinically used anticancer agents, e.g. taxol and vincristine. Among natural products, mangrove-derived fungi are of particular scientific interest evidenced by the increasing rate of publications on cytotoxic secondary metabolites reported. Hence, this literature review aims to provide comprehensive information on cytotoxic secondary metabolites isolated from mangrove-derived fungi, which might contribute to the search for anticancer leads from natural resources. Data were collected from original research articles published on scientific-based sources such as Google Scholar, PubMed, Taylor and Francis, Elsevier, and MDPI, in the range of 2011-2022. Fifty-four cytotoxic secondary metabolites with IC50 values below 10 µM were described herein, which were classified in to 8 groups of metabolites. These compounds were reported from 16 genera of mangrove-associated fungi. Among them, Aspergillus and Penicillium were the most frequent producers of cytotoxic metabolites, suggesting their enormous potential as a source of pharmacophores for anticancer candidates.